2018
DOI: 10.3389/fenvs.2018.00087
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Mucilage in the Rhizosphere Measured With Infrared Spectroscopy

Abstract: Mucilage is receiving increasing attention because of its putative effects on plant growth, but so far no method is available to measure its spatial distribution in the rhizosphere. We tested whether the C-H signal related to mucilage fatty acids is detectable by infrared spectroscopy and if this method can be used to determine the spatial distribution of mucilage in the rhizosphere. Maize plants were grown in rhizoboxes filled with soil free of organic matter. Infrared measurements were carried out along tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 28 publications
5
15
0
Order By: Relevance
“…The simulated radial extent of citrate and mucilage rhizopheres in which the rhizodeposit concentration was below the threshold value, but still detectable, was 4 – 9 mm and 2 – 5 mm , respectively. For mucilage, these values are in the same range as the experimental findings by Holz et al (2018a) and the calculated values by Zickenrott et al (2016), who reported rhizosphere extents between 0.6 mm and 2 mm . For citrate, the radial rhizosphere extents are in the same order of magnitude as the results for rhizodeposited 14 C by Kuzyakov et al (2003), who measured a zone of maximum carbon exudate concentration within a distance of 1 – 2 mm from the root surface and a zone of less significant amounts of carbon exudate concentration within a distance of 3 – 10 mm from the root surface.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The simulated radial extent of citrate and mucilage rhizopheres in which the rhizodeposit concentration was below the threshold value, but still detectable, was 4 – 9 mm and 2 – 5 mm , respectively. For mucilage, these values are in the same range as the experimental findings by Holz et al (2018a) and the calculated values by Zickenrott et al (2016), who reported rhizosphere extents between 0.6 mm and 2 mm . For citrate, the radial rhizosphere extents are in the same order of magnitude as the results for rhizodeposited 14 C by Kuzyakov et al (2003), who measured a zone of maximum carbon exudate concentration within a distance of 1 – 2 mm from the root surface and a zone of less significant amounts of carbon exudate concentration within a distance of 3 – 10 mm from the root surface.…”
Section: Discussionsupporting
confidence: 88%
“…For citrate, the maximum simulated radial hotspot extent of 1 mm and the detectable concentration extent of 4 − 9 mm were of the same order of magnitude as the results for rhizodeposited 14 C from Kuzyakov et al (2003) who measured a zone of maximum carbon exudate concentration at a distance of 1 − 2 mm from the root surface and a zone of less significant amounts of carbon exudate concentration at a distance of − mm from the root surface. It must be noted that the experimental conditions and model assumptions in the studies by Holz et al (2018a), Zickenrott et al (2016) and Kuzyakov et al (2003) were not the same as in our modelling setup. They differed with regard to plant species, plant age, water content and pot geometry and may therefore only be regarded as an indicative of the order of magnitude.…”
Section: Rhizodeposition By a Single Growing Rootmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus, homogenized mucilage samples may not reflect the properties of Chia seed mucilage in natural conditions. The observed spatial heterogeneity in OM composition (in terms of relative C–H group content) corresponds with that observed by micro‐FTIR across root channels of maize seedlings ( Holz et al., ). As assumed by Carvalhais et al.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, homogenized mucilage samples may not reflect the properties of Chia seed mucilage in natural conditions. The observed spatial heterogeneity in OM composition (in terms of relative C-H group content) corresponds with that observed by micro-FTIR across root channels of maize seedlings (Holz et al, 2018). As assumed by Carvalhais et al (2011) and Ahmed et al (2015), mucilage composition may be affected by growing conditions of the plants such that the composition of the excreted mucilage may vary with time causing heterogeneity in OM composition in space.…”
Section: Spatial Heterogeneity Of Mucilage Compositionsupporting
confidence: 73%